2021
DOI: 10.1038/s41419-020-03288-x
|View full text |Cite
|
Sign up to set email alerts
|

The HSP GRP94 interacts with macrophage intracellular complement C3 and impacts M2 profile during ER stress

Abstract: The role of GRP94, an endoplasmic reticulum (ER) stress protein with both pro- and anti-inflammatory functions, has not been investigated in macrophages during ER stress, whereas ER stress has been reported in many diseases involving macrophages. In this work, we studied GRP94 in M1/LPS + IFNγ and M2/IL-4 primary macrophages derived from human monocytes (isolated from buffy coats), in basal and ER stress conditions induced by thapsigargin (Tg), an inducer of ER calcium depletion and tunicamycin (Tm), an inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 42 publications
(51 reference statements)
3
27
0
Order By: Relevance
“…Moreover, Kwon et al ( 123 ) analyzed the interactions of HCV E2 with human monocyte-derived macrophages and showed that it induced a polarization of macrophages toward an M2-like anti-inflammatory phenotype, which is consistent with the increase in TGF-β production by hepatocytes. Although they did not study GRP94 specifically, we can hypothesize that E2 also induces AIMP1 degradation and GRP94 migration to the cell membrane in macrophages, consistent with our findings in which we showed that membrane GRP94 is a signature of M2 macrophages ( 105 ).…”
Section: Glucose-regulated Proteins Grp78 and Grp94 In Viral Infectionsupporting
confidence: 91%
See 2 more Smart Citations
“…Moreover, Kwon et al ( 123 ) analyzed the interactions of HCV E2 with human monocyte-derived macrophages and showed that it induced a polarization of macrophages toward an M2-like anti-inflammatory phenotype, which is consistent with the increase in TGF-β production by hepatocytes. Although they did not study GRP94 specifically, we can hypothesize that E2 also induces AIMP1 degradation and GRP94 migration to the cell membrane in macrophages, consistent with our findings in which we showed that membrane GRP94 is a signature of M2 macrophages ( 105 ).…”
Section: Glucose-regulated Proteins Grp78 and Grp94 In Viral Infectionsupporting
confidence: 91%
“…In these cells, functional GRP94 was secreted under ER stress conditions, and this correlated with a switch to a proinflammatory profile which was dependent on activation of the UPR through IRE1α. Under these conditions, GRP94 is cosecreted with C3 and may facilitate its cleavage by cathepsin L. We also showed that GRP94 interacts directly with cathepsin L ( 105 ). Finally, GRP94 controls regulatory T cells by chaperoning GARP (glycoprotein A repetitions predominant), the docking receptor for transforming growth factor beta (TGF-β) ( 115 ) and the integrins αvβ6 and β8 involved in its release.…”
Section: Glucose-regulated Proteins Grp78 and Grp94 In Viral Infectionmentioning
confidence: 66%
See 1 more Smart Citation
“…We first used immunofluorescence to confirm previous preliminary results showing the presence of CD206 + M2-like macrophages in 4T1 biopsies, among which, 44% highly expressed GRP94 [9]. As shown in Figure 1A, CD206 + macrophages were present in the 4T1 biopsies analyzed and 35.8% ± 6.40% co-expressed GRP94 in coherence with our previous results.…”
Section: Grp94 Is Co-expressed By Cd206 + M2-like Macrophages In Murine 4t1 and Human Tnbc Infiltrated With Cd206 + Cellssupporting
confidence: 87%
“…Consequently, sGARP could be considered a new soluble factor favoring M2 polarization, which also supports an immunosuppressive TME. Of note, we have shown that primary human M2 macrophages do not express GARP at their membranes, although they produce TGF-β [ 72 ] and, to our knowledge, M2-like macrophages in the TME have not been reported to express GARP.…”
Section: Garp In Cancermentioning
confidence: 99%